PEDAGOGICAL SUPPORT IN THE SYSTEM OF CONTINUOUS EDUCATION AS THE BASIS OF ADAPTIVE-PRODUCTIVE DEVELOPMENT OF PERSONALITY - N. Balitskaya; N. Kozyrev; O. Kozyreva (Вестник Северо-Кавказского федерального университета, 2022)
In article the bases of statement and the solution of problems of theorization of opportunities of pedagogical support in the system of continuous education opening age-corresponding personal development in the context of adaptive and productive opportunities of training, formation and formation of the personality are defined. Are specified in broad, narrow and local meanings the concept «adaptive and productive personal development», bases of statement and the solution of problems of the choice of model, methods and technologies of pedagogical support in adaptive and productive personal development in the system of continuous education are opened. Stages of age-corresponding, adaptive and productive personal development in the SPO, VO, DPO system are defined. Pedagogical conditions of improvement of quality and effectiveness of adaptive and productive personal development in the system of continuous education are proved in modeling and design, specification and realization.